SARS-CoV-2/COVID-19 Testing: The Tower of Babel - Reno, Chiara; Lenzi, Jacopo; Golinelli, Davide; Gori, Davide; Signorelli, Carlo; Kraemer, John; Stoto, Michael A.; Avitabile, Elisa; Landini, Maria Paola; Lazzarotto, Tiziana; Re, Maria Carla; Rucci, Paola; et al. (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: Testing represents one of the main pillars of public health response to SARS-CoV-2/COVID-19 pandemic. This paper shows how accuracy and utility of testing programs depend not just on the type of tests, but on the context as well. Methods: We describe the testing methods that have been developed and the possible testing strategies; then, we focus on two possible methods of population-wide testing, i.e., pooled testing and testing with rapid antigen tests. We show the accuracy of split-pooling method and how, in different pre-test probability scenarios, the positive and negative predictive values vary using rapid antigen tests. Results: Split-pooling, followed by retesting of negative results, shows a higher sensitivity than individual testing and requires fewer tests. In case of low pre-test probability, a negative result with antigen test could allow to rule out the infection, while, in case of a positive result, a confirmatory molecular test would be necessary. Conclusions: Test performance alone is not enough to properly choose which test to use; goals and context of the testing program are essential. We advocate the use of pooled strategies when planning population-wide screening, and the weekly use of rapid tests for close periodic monitoring in low-prevalence populations.